Additive manufacturing: DED process parameters optimisation via simulation - Quek, Derek Zong Xun (Nanyang Technological University, 2023)
With the increasing popularity of Additive Manufacturing in recent years, there has been a growing focus on optimising its processes to leverage its numerous benefits over traditional subtractive manufacturing. Among the various additive manufacturing techniques, Directed Energy Deposition (DED) is the most prevalent, and extensive research is being carried out to optimise its operational parameters towards achieving multi-objective optimisation, thereby revolutionising the industry.